Inovasi Kurikulum Bisnis di Sekolah Dasar Alam Baturraden - Rosyadi, Agung Anas; Purwanda, Eka (LPPM Institut Pendidikan Nusantara Global, 2024)
The aim of this research is to describe the innovation of the business curriculum and its application at Sekolah Dasar Alam Baturraden. Educational institutions need to innovate in their curriculum to accommodate the provision of knowledge about entrepreneurship, along with teaching strategies that can shape students' entrepreneurial mindset. The thinking of elementary school students aged between 7-12 years is still malleable and can be shaped according to the needs of their environment. Therefore, it is essential to instill and develop a mindset where students aspire to become entrepreneurs. The research findings show that business curriculum innovation can be described as new ideas and concepts in the form of business learning methods that nurture and develop entrepreneurial spirit with the aim of financial independence. The application of business curriculum innovation at SD Alam Baturraden includes business learning methods such as market day, business day, business internships, business presentations, social projects (fundraising), and business mentoring.